Sources on Jewish Self-Government in the Polish Lands from Its Inception to the Present - Guesnet, François,; Tomaszewski, Jerzy, (Religious Studies, Theology and Philosophy E-Books Online, Collection 2022, ISBN: 9789004507777., 2022)
This source-reader invites you to encounter the world of one thousand years of Jewish self-government in eastern Europe. It tells about the beginnings in the Middle Ages, delves into the unfolding of communal hierarchies and supra-communal representation in the early modern period, and reflects on the impact of the partitions of the Polish-Lithuanian Commonwealth and of growing state interference, as well as on the communist and post-communist periods. Translated into English from Hebrew, Latin, Yiddish, Polish, Russian, German, and other languages, in most cases for the first time, the sources illustrate communal life, the interdependence of civil and religious leadership, the impact of state legislation, Jewish-non-Jewish encounters, reform projects and political movements, but also Jewish resilience during the Holocaust.